Prevalence of educational needs and factors associated with educational severity among Rohingya refugee children in Cox’s Bazar, Bangladesh: A representative cross-sectional household survey - Harry J. Wilson; Nyanhial Yang; Md Nazmul Karim (PLOS Global Public Health, 2026)
Approximately 1.2 million Rohingya refugees currently reside among the 33 refugee camps in Cox’s Bazar - Bangladesh, where the right to education remains a critical humanitarian concern. This study aimed to estimate the prevalence of Rohingya refugee children in educational need, elucidate predominant reasons among children in need, and identify factors associated with educational severity to inform targeted humanitarian relief efforts. This study utilized participant data collected during the 2023 Joint Multi-Sectoral Needs Assessment - a representative cross-sectional household survey. Education-age children (3–18) were assigned a severity score categorized as stressed, severe, or extreme based on proxy responses capturing educational access, learning conditions, and protection factors. Ordinal logistic regression examined factors associated with increasing educational severity scores. Among 8,408 education age children surveyed from 2,959 households, 29.6% were in severe educational need and 10.1% were in extreme educational need. After adjustment, increasing educational severity was significantly associated with head of household age 45–59 (aOR= 1.29 [95%CI: 1.09–1.54]), head of household age 60+ (aOR= 1.31 [95%CI: 1.07–1.60]), female headed households (aOR= 1.33 [95%CI: 1.15–1.54]), early education age boys (aOR= 3.95 [95%CI: 3.21–4.85]) and teenage boys (aOR= 4.42 [95%CI: 3.73–5.24]) relative to primary school age boys, early education age girls (aOR= 4.23 [95%CI: 3.36–5.31]) and teenage girls (aOR= 19.06 [95%CI: 15.70–23.15]) relative to primary school age girls, primary school age girls (aOR= 0.82 [95%CI: 0.68–0.99]) relative to primary school age boys, and teenage girls (aOR= 3.54 [95%CI: 3.04–4.12]) relative to teenage boys. Educational needs remain highly prevalent among Rohingya refugee children – particularly teenage girls. Local humanitarian authorities are currently providing targeted relief to those in educational need but these interventions are threatened by sweeping international funding cuts. Future longitudinal studies are required to monitor educational needs over time and further clarify causal pathways.